1978
DOI: 10.1152/jappl.1978.45.5.733
|View full text |Cite
|
Sign up to set email alerts
|

Flow dependence of gas distribution and the pattern of inspiratory muscle contraction

Abstract: We measured regional distribution of xenon-133 boli at 0.25, 0.75, and 1.5 l/s in four normal seated subjects during inspirations performed predominantly with intercostal and accessory muscles (IC) or with the diaphragm, accompanied by outward abdominal motion (Ab). In six additional subjects we inferred the topographical distribution of helium boli during similar breaths and flow rates from the slope of the alveolar plateau recorded during a slow expiration (less than 0.5 l/s). Distribution of the helium boli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Flow dependence of gas distribution, as we measured it, is partly due to different patterns of inspiratory muscle recruitment with high flow maneuvers using rib cage muscles more than low flow maneuvers (24). Therefore in our patient the lack of flow dependence suggested that the pattern of recruitment, emphasizing nondiaphragmatic muscles normally employed at high flow rates, was already operative on the paralyzed side at low flow rates, and persisted without change as flow increased.…”
Section: Regional Distribution Of Boluses Inhaled At Frcmentioning
confidence: 60%
“…Flow dependence of gas distribution, as we measured it, is partly due to different patterns of inspiratory muscle recruitment with high flow maneuvers using rib cage muscles more than low flow maneuvers (24). Therefore in our patient the lack of flow dependence suggested that the pattern of recruitment, emphasizing nondiaphragmatic muscles normally employed at high flow rates, was already operative on the paralyzed side at low flow rates, and persisted without change as flow increased.…”
Section: Regional Distribution Of Boluses Inhaled At Frcmentioning
confidence: 60%
“…1967) and (c) tidal pleural pressure variation (BAKEet a]. , FIXLEY et al 1978. The influence of each of these factors will be discussed in the following paragraphs.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the participants learned the following breathing exercises which were randomized (computer program): diaphragmatic breathing - the participants had to perform a slow and deep nasal inspiration emphasizing the anterior displacement of the abdomen and avoiding RC displacement 4 , 22 ; inspiratory sighs - short, successive, and slow nasal inspirations until the inspiratory capacity was reached 7 ; sustained maximal inspiration - a slow nasal maximal inspiratory effort to reach the inspiratory capacity, followed by a 3-second post-inspiratory pause 23 ; and intercostal breathing - nasal inspiration emphasizing the displacement of the upper portion of the thorax 9 . For the diaphragmatic breathing, inspiratory sighs, and maximal inspiration, the subjects were instructed to perform a smooth and controlled pursed lip expiration.…”
Section: Methodsmentioning
confidence: 99%
“…inspiratory sighs) or maximal inspiratory effort 7 , 8 . In addition, the intercostal breathing exercise emphasizes rib cage (RC) compartment muscles, promoting greater displacement of this compartment 8 , 9 . Cuello et al 8 was the first to propose the use of inspiratory sighs and intercostal breathing exercises 8 .…”
Section: Introductionmentioning
confidence: 99%